Interactive Software Technology for Deaf Users: Mapping the HCI Research Landscape that Focuses on Accessibility - Yeratziotis, Alexandros; Zaphiris, Panayiotis (My University, 2015)
The purpose of this paper is to chart research developments in HCI literature that focuses on accessibility for the deaf user group. A map for this particular landscape has been constructed based on a review of the four most relevant sources in HCI that focuses on accessibility, from 2000 to 2013. The map describes topics of research that are covered under the umbrella of Interactive Software Technology (IST) for deaf users in HCI literature that focuses on accessibility. To construct the map and identify these topics a systematic approach was applied, involving a number of stages and employing several research methods (literature review, focus group and card sorting). The resulting map, which underwent three revisions, consists of 23 code categories in total: 3 main categories, 8 subcategories, 7 second-level subcategories and 5 third-level subcategories. This paper can act as a guide for other researchers interested in conducting research within this landscape.
Keywords: Map; Deaf user; HCI; Accessibility; Interactive software technology